Biodegradable In Situ Gel-Forming Controlled Drug Delivery System Based on Thermosensitive Poly(ε-caprolactone)-Poly(ethylene glycol)-Poly(ε-caprolactone) Hydrogel. (27th November 2012) - Khodaverdi, Elham; Golmohammadian, Ali; Mohajeri, Seyed Ahmad; Zohuri, Gholamhossein; Mirzazadeh Tekie, Farnaz Sadat; Hadizadeh, Farzin
Abstract : Traditional drug delivery systems which are based on multiple dosing regimens usually pose many disadvantages such as poor compliance of patients and drug plasma level variation. To overcome the obstacles of traditional drug formulations, novel drug delivery system PCL-PEG-PCL hydrogels have been purposed in this study. Copolymers were synthesized by rapid microwave-assisted and conventional synthesis methods. Polymer characterizations were done using gel permeation chromatography and 1 H-NMR. Phase transition behavior was evaluated by inverting tube method and in vitro drug release profile was determined using naltrexone hydrochloride and vitamin B12 as drug models. The results indicated that loaded drug structure and copolymer concentration play critical roles in release profile of drugs from these hydrogels. This study also confirmed that synthesis of copolymer using microwave is the most effective method for synthesis of this kind of copolymer.